1984
DOI: 10.2165/00003088-198409020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Labetalol

Abstract: Labetalol was the first of a new class of antihypertensive drugs with both alpha- and beta-adrenoceptor blocking properties present in the same molecule. Its efficacy has been confirmed by double-blind studies in the treatment of all grades of hypertension and in angina pectoris. The drug's major dose-related side effect is postural hypotension. The clinical formulation of labetalol consists of equal proportions of 4 optical isomers. One of these (the RR isomer) is probably responsible for the drug's beta-adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 38 publications
(21 reference statements)
1
36
1
Order By: Relevance
“…After a single dose of labetalol, the plasma concentration versus time profile shows marked variation between individuals and there is no uniform relationship between the plasma concentra tion and the fall in BP; it has been concluded that individual sensitivity to the drug plays a major role in determining the BP response [81-In this study, the antihypertensive effect of labetalol in the normotensive subjects was clear-cut. The mean drop in MAP was 16%, which agrees with previous studies with the same dose of intravenous labetalol [4,7], The antihypertensive effect remained mea surable for more than 1 h. Labetalol has one major side effect, postural hypotension [8], and 1 of our 10 subjects complained of slight dizziness during the study; the fall in BP in that case was 44%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After a single dose of labetalol, the plasma concentration versus time profile shows marked variation between individuals and there is no uniform relationship between the plasma concentra tion and the fall in BP; it has been concluded that individual sensitivity to the drug plays a major role in determining the BP response [81-In this study, the antihypertensive effect of labetalol in the normotensive subjects was clear-cut. The mean drop in MAP was 16%, which agrees with previous studies with the same dose of intravenous labetalol [4,7], The antihypertensive effect remained mea surable for more than 1 h. Labetalol has one major side effect, postural hypotension [8], and 1 of our 10 subjects complained of slight dizziness during the study; the fall in BP in that case was 44%.…”
Section: Discussionsupporting
confidence: 90%
“…The pharmacodynamics of labetalol have been fairly well investigated in nonpregnant and pregnant women [6][7][8]. After a single dose of labetalol, the plasma concentration versus time profile shows marked variation between individuals and there is no uniform relationship between the plasma concentra tion and the fall in BP; it has been concluded that individual sensitivity to the drug plays a major role in determining the BP response [81-In this study, the antihypertensive effect of labetalol in the normotensive subjects was clear-cut.…”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82] Table 3 summarizes the pharmacokinetic characteristics of the most frequently used antihypertensive drugs belonging to the 5 main classes. [83][84][85][86][87][88][89][90][91][92][93] Drug monitoring may also be influenced by preanalytical errors. False-negative results might be because of nonspecific drug adsorption on the plastic tube or separator gel used or to drug instability at higher temperature or sensitivity to light as described for nifedipine.…”
Section: Influence Of Pharmacokinetics and Preanalytical Errors On Drmentioning
confidence: 99%
“…Labetolol was introduced to the market in 1984 and since then has been used extensively to treat severe hypertension. Some authors recommend it for patients with chronic renal failure [11,12].…”
Section: Discussionmentioning
confidence: 99%